2005
DOI: 10.1677/jme.1.01628
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of transcriptional regulation of LRP16 gene expression by 17-β estradiol in MCF-7 human breast cancer cells

Abstract: LRP16 gene expression is induced by 17-estradiol (E2) via estrogen receptor alpha (ER ) in MCF-7 human breast cancer cells. A previous study also demonstrated that ectopic expression of LRP16 gene promoted MCF-7 cell proliferation. To explore the mechanism of hormone-induced LRP16 gene expression, the LRP16 gene promoter region (-2600 to -24 bp upstream of the LRP16 gene translation starting site) was analyzed in the present study by using different 58-truncated constructs, and a luciferase reporter. The 58-fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 51 publications
(54 reference statements)
0
43
1
Order By: Relevance
“…For example, studies in this laboratory and others have demonstrated that deletion and mutational analysis of promoters derived from several E 2 -responsive genes contain GC-rich motifs that bind Sp proteins (Safe & Kim 2004). Some of the genes that fall into this category are important for cell proliferation, angiogenesis, and nucleotide metabolism and include E 2 F1, retinoic acid receptor a (RARa), carbamoylphosphate synthetase/ aspartate transcarbamylase/dihydroorotase (CAD), bcl-2, DNA polymerase a, vascular endothelial growth factor (VEGF), VEGFR receptor 2 (VEGFR2), progesterone receptor, creatine kinase B, thymidylate synthase, insulinlike growth factor binding protein 4, epidermal growth factor receptor, receptor for advanced glycation end products, low density lipoprotein receptor, vitamin D receptor, pS2, LRP16, metastasis associated protein 3, and SK3 (Porter et al 1996, Duan et al 1998, Sun et al 1998, 2005, Qin et al 1999, Xie et al 1999, 2000, Byrne et al 2000, Salvatori et al 2000, Saville et al 2000, Stoner et al 2000, Tanaka et al 2000, Castro-Rivera et al 2001, Li et al 2001, Bruning et al 2003, Jacobson et al 2003, Khan et al 2003, Ngwenya & Safe 2003, Schultz et al 2003, 2005, Fujita et al 2004, Bardin et al 2005, Zhao et al 2005, Higgins et al 2006b). In addition, RNA interference studies with a small inhibitory RNA (siRNA) for Sp1 (iSp1) show that after transfection with iSp1, there was a significant decrease in hormone-induced G 0 /G 1 to S-phase progression, suggesting that ERa/Sp1 plays an important role in this process (Abdelrahim et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies in this laboratory and others have demonstrated that deletion and mutational analysis of promoters derived from several E 2 -responsive genes contain GC-rich motifs that bind Sp proteins (Safe & Kim 2004). Some of the genes that fall into this category are important for cell proliferation, angiogenesis, and nucleotide metabolism and include E 2 F1, retinoic acid receptor a (RARa), carbamoylphosphate synthetase/ aspartate transcarbamylase/dihydroorotase (CAD), bcl-2, DNA polymerase a, vascular endothelial growth factor (VEGF), VEGFR receptor 2 (VEGFR2), progesterone receptor, creatine kinase B, thymidylate synthase, insulinlike growth factor binding protein 4, epidermal growth factor receptor, receptor for advanced glycation end products, low density lipoprotein receptor, vitamin D receptor, pS2, LRP16, metastasis associated protein 3, and SK3 (Porter et al 1996, Duan et al 1998, Sun et al 1998, 2005, Qin et al 1999, Xie et al 1999, 2000, Byrne et al 2000, Salvatori et al 2000, Saville et al 2000, Stoner et al 2000, Tanaka et al 2000, Castro-Rivera et al 2001, Li et al 2001, Bruning et al 2003, Jacobson et al 2003, Khan et al 2003, Ngwenya & Safe 2003, Schultz et al 2003, 2005, Fujita et al 2004, Bardin et al 2005, Zhao et al 2005, Higgins et al 2006b). In addition, RNA interference studies with a small inhibitory RNA (siRNA) for Sp1 (iSp1) show that after transfection with iSp1, there was a significant decrease in hormone-induced G 0 /G 1 to S-phase progression, suggesting that ERa/Sp1 plays an important role in this process (Abdelrahim et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A proximal region of K676 to K24 bp of the human LRP16 promoter was previously identified to be essential for estrogen induction of LRP16 expression in MCF-7 cells (Han et al 2008). Estrogen induces LRP16 gene transactivation by stimulating the interaction and recruitment of ERa and Sp1 transcription factor at a 1/2 ERE/ GC-rich site and multiple GC-rich sites present in K676 to K24 bp of the upstream regulatory region of LRP16 gene (Zhao et al 2005, Han et al 2008. By promoter analysis, we demonstrate that the fragment from K676 to K214 bp of the LRP16 upstream regulatory region mainly confers estrogen-repressed effect of LRP16 expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…BG-1 human ovarian epithelial cancer cell line was cultured as previously described (Geisinger et al 1989). Steroid-deprived serum was prepared as previously described (Zhao et al 2005). …”
Section: Chemicals and Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations